A newly isolated Trichoderma Parareesei N4-3 exhibiting a biocontrol potential for banana fusarium wilt by Hyperparasitism - Long, Weiqiang; Chen, Yufeng; Wei, Yongzan; Feng, Junting; Zhou, Dengbo; Cai, Bingyu; Qi, Dengfeng; Zhang, Miaoyi; Zhao, Yankun; Li, Kai; Liu, Yong-Zhong; Wang, Wei; et al. (Frontiers in Plant Science, 2023)
Banana Fusarium wilt caused by Fusarium oxysporum f. sp. cubense tropical race4 (Foc TR4) is one of the most destructive soil-borne fungal diseases and currently threatens banana production around the world. Until now, there is lack of an effective method to control banana Fusarium wilt. Therefore, it is urgent to find an effective and eco-friendly strategy against the fungal disease. In this study, a strain of Trichoderma sp. N4-3 was isolated newly from the rhizosphere soil of banana plants. The isolate was identified as Trichoderma parareesei through analysis of TEF1 and RBP2 genes as well as morphological characterization. In vitro antagonistic assay demonstrated that strain N4-3 had a broad-spectrum antifungal activity against ten selected phytopathogenic fungi. Especially, it demonstrated a strong antifungal activity against Foc TR4. The results of the dual culture assay indicated that strain N4-3 could grow rapidly during the pre-growth period, occupy the growth space, and secrete a series of cell wall-degrading enzymes upon interaction with Foc TR4. These enzymes contributed to the mycelial and spore destruction of the pathogenic fungus by hyperparasitism. Additionally, the sequenced genome proved that strain N4-3 contained 21 genes encoding chitinase and 26 genes encoding β-1,3-glucanase. The electron microscopy results showed that theses cell wall-degrading enzymes disrupted the mycelial, spore, and cell ultrastructure of Foc TR4. A pot experiment revealed that addition of strain N4-3 significantly reduced the amount of Foc TR4 in the rhizosphere soil of bananas at 60 days post inoculation. The disease index was decreased by 45.00% and the fresh weight was increased by 63.74% in comparison to the control. Hence, Trichoderma parareesei N4-3 will be a promising biological control agents for the management of plant fungal diseases.